Dysfunction of the gastrointestinal tract in infants of first of life with severe perinatal brain lesion - E. V. Shimchenko; E. I. Kleshchenko (Кубанский научный медицинский вестник, 2015)
The article presents various manifestations of gastrointestinal dysfunction in children with severe perinatal brain lesion. The observation included thirty infants at the age of one to six months and thirty three infants at the age of six to twelve months. The effect of the specialised therapeutic formulas on the functional state of the digestive organs, physical development in infants of first year of life was studied and assessed.